Direct Versus Video Laryngoscopy Using the C‐MAC for Tracheal Intubation in the Emergency Department, a Randomized Controlled Trial. (24th March 2016) - Driver, Brian E.; Prekker, Matthew E.; Moore, Johanna C.; Schick, Alexandra L.; Reardon, Robert F.; Miner, James R.
Abstract: Background: Direct laryngoscopy (DL) has long been the most common approach for emergency endotracheal intubation, although the use of video laryngoscopy (VL) is becoming more widespread. Current observational data suggest that VL has higher first‐pass success, although randomized trials are lacking. Objectives: The objective was to compare first‐pass success in patients undergoing emergency intubation with DL or VL using a C‐MAC device. Methods: This was an open‐label, prospective, randomized, controlled trial in an academic emergency department of patients undergoing emergency intubation with a plan of DL for the first attempt. Patients were randomly assigned in a 1:1 ratio to either DL or VL using a C‐MAC device for the first intubation attempt. The primary outcome was first‐pass success. Secondary outcomes included time to intubation, development of aspiration pneumonia, and hospital length of stay (LOS). The study was registered at Clinicaltrials.gov, number NCT01710891. Results: A total of 198 patients were enrolled and intubated with either DL ( n = 95) or VL ( n = 103). First‐attempt success was 86 and 92% for the DL and VL groups, respectively (difference = −5.9%, 95% confidence interval = −14.5% to 2.7%, p = 0.18). Time to intubation, rates of aspiration pneumonia, and hospital LOS were not different between the two groups. Conclusions: In patients undergoing emergency intubation in whom DL was planned for the first attempt, we did not detect a difference between VL or DL using the C‐MAC device in first‐pass success, duration of intubation attempt, aspiration pneumonia, or hospital LOS.